BET inhibition therapy counteracts cancer cell survival, clonogenic potential and radioresistance mechanisms in rhabdomyosarcoma cells. (1st June 2020) - Camero, Simona; Camicia, Lucrezia; Marampon, Francesco; Ceccarelli, Simona; Shukla, Rajeev; Mannarino, Olga; Pizer, Barry; Schiavetti, Amalia; Pizzuti, Antonio; Tombolini, Vincenzo; Marchese, Cinzia; Dominici, Carlo; et al.
Abstract: The antitumour effects of OTX015, a first-in-class BET inhibitor (BETi), were investigated as a single agent or in combination with ionizing radiation (IR) in preclinical in vitro models of rhabdomyosarcoma (RMS), the most common childhood soft tissue sarcoma. Herein, we demonstrated the upregulation of BET Bromodomain gene expression in RMS tumour biopsies and cell lines compared to normal skeletal muscle. In vitro experiments showed that OTX015 significantly reduced RMS cell proliferation by altering cell cycle modulators and apoptotic related proteins due to the accumulation of DNA breaks that cells are unable to repair. Interestingly, OTX015 also impaired migration capacity and tumour-sphere architecture by downregulating pro-stemness genes and was able to potentiate ionizing radiation effects by reducing the expression of different drivers of tumour dissemination and resistance mechanisms, including the GNL3 gene, that we correlated for the first time with the RMS phenotype. In conclusion, our research sheds further light on the molecular events of OTX015 action against RMS cells and indicates this novel BETi as an effective option to improve therapeutic strategies and overcome the development of resistant cancer cells in patients with RMS. Highlights: The antitumour activity of OTX015 in alveolar rhabdomyosarcoma (ARMS) was investigated. OTX015 reduced ARMS cell proliferation and induced apoptosis by blocking AKT activation and upregulating miR-124-3p levels. OTX015 impaired cancer stemness properties and radiosensitise ARMS cells. . GNL3 aberrant upregulation correlated with MYC expression and ARMS tumour stage. OTX015 represents a therapeutic option to improve clinical treatments against ARMS tumours.